Chemical Welding of the Electrode–Electrolyte Interface by Zn‐Metal‐Initiated In Situ Gelation for Ultralong‐Life Zn‐Ion Batteries. Issue 44 (3rd October 2022) - Qin, Yao; Li, Hongfei; Han, Cuiping; Mo, Funian; Wang, Xin
Abstract: A compatible and robust electrode–electrolyte interface is favorable in resolving the severe dendritic growth and side reactions of aqueous Zn‐ion batteries toward commercial‐standard lifespan and charging–discharging rate. Herein, a chemical welding strategy through in situ construction of a gel electrolyte that enables Zn‐ion batteries to achieve ultralong life and reversibility is reported. The gel electrolyte is spontaneously formed on the Zn anode surface by redox polymerization with the initiation of Zn metal. The direct participation of the Zn anode in the chemical synthesis of the gel electrolyte brings a well‐bonded and water‐poor electrode–electrolyte interface, which not only alleviates side reactions but also enables preferential (002) Zn deposition. The in situ symmetric cell thus prepared delivers an ultralong lifespan of 5100 h (>212 days), and a hybrid capacitor with the in situ electrolyte runs smoothly over 40 000 cycles at 20 A g −1 . Even at an ultrahigh current density of 40 mA cm −2  and capacity of 40 mAh cm −2, the cell still operates stably for 240 h, alongside a high Zn utilization with 87% depth of discharge. The in situ gel electrolyte integrating robust interface and preparation of all‐in‐one cells demonstrate a commercializable path for aqueous Zn‐storage devices. Abstract : The in situ gel electrolyte initiated by Zn metal produces chemical welding between the anode and the electrolyte, enabling a well‐bonded and water‐poor electrode–electrolyte interface that suppresses the growth of Zn dendrites and side reactions while improving the Zn utilization up to 87%. The as‐prepared cells showcase superior cycling stability, with an ultralong life of over 212 days.